Conocemos costumbres y tradiciones que tenemos en común - Pérez Vásquez, Dante Rubén (2019)
Nowadays the group of actions that family and school perform to achieve the complete development of children, it’s considered as a complex process that children’s life require, being the school level the base; both institutions acquire new interactions that are conditioned for the transformations that occur in the modern society, which they have a decisive impact in the learning process where children are part._x000D_ For that, to make a research related to the participation of the family in the education of values, rights, has a particular relevance to determinate some strategies of intervention that contribute significantly to reinforce the chain, family- school._x000D_ The following report has as a title “Knowing customs and craditions that we have in common”, was designed for students of second grade of primary education._x000D_ The introduction is aimed to the planning of the class, the assessment of the performance, the evidence of learning and the instrument of evaluation to use, furthermore, the teaching sequence that is used in the area of Social Studies, which allows children to develop competences to elaborate and face rules; our self- appreciation and the consolidation of our identity that allow to life in democracy and participate in our community as of the deliberation of topics that involve us. In the same way, ethic, understand as the compromise with moral principles such as the caring of others, is essential to generate a harmonious coexistence that recognize and respect others and find common welfare._x000D_ In the second chapter it is presented the substantiation of the area of Social Studies, according to the new curriculum framework, considering the profile of graduation that the student has to achieve to conclude the Regular Basic Education and the approaches that guide them._x000D_ In the third chapter, it’s dedicated to the pedagogical sustenance, related to the psycho-pedagogical sustenance, pedagogical procedures, didactic procedures, of technic areas, resources and materials in the methodological process, and the procedures and instruments of evaluation.